Construing Morality at High versus Low Levels Induces Better Self-control, Leading to Moral Acts - Wu, Chia-Chun; Wu, Wen-Hsiung; Chiou, Wen-Bin (Frontiers in Psychology, 2017)
Human morality entails a typical self-control dilemma in which one must conform to moral rules or socially desirable norms while exerting control over amoral, selfish impulses. Extant research regarding the connection between self-control and level of construal suggest that, compared with a low-level, concrete construal (highlighting means and resources, e.g., answering ‘how’ questions), a high-level, abstract construal (highlighting central goals, e.g., answering ‘why’ questions) promotes self-control. Hence, construing morality at higher levels rather than lower levels should engender greater self-control and, it follows, promote a tendency to perform moral acts. We conducted two experiments to show that answering “why” (high-level construal) vs. “how” (low-level construal) questions regarding morality was associated with a situational state of greater self-control, as indexed by less Stroop interference in the Stroop color-naming task (Experiments 1 and 2). Participants exposed to “why” questions regarding morality displayed a greater inclination for volunteerism (Experiment 1), showed a lower tendency toward selfishness in a dictator game (Experiment 2), and were more likely to return undeserved money (Experiment 2) compared with participants exposed to “how” questions regarding morality. In both experiments, self-control mediated the effect of a high-level construal of morality on dependent measures. The current research constitutes a new approach to promoting prosociality and moral education. Reminding people to think abstractly about human morality may help them to generate better control over the temptation to benefit from unethical acts and make it more likely that they will act morally.